Prognostic impact of hospital‐acquired disability in elderly patients with heart failure. (10th April 2021) - Saitoh, Masakazu; Takahashi, Yuta; Okamura, Daisuke; Akiho, Mitsutoshi; Suzuki, Hidetoshi; Noguchi, Naoki; Yamaguchi, Yukito; Hori, Kentaro; Adachi, Yuichi; Takahashi, Tetsuya
Abstract: Aims: Functional decline is associated with worse outcomes in patients with elderly heart failure (HF), but little is known about the prognostic impact of hospital‐acquired disability (HAD) during hospital stay after acute HF. The present study examines the prognostic significance of HAD in the prediction of all‐cause mortality in elderly patients who admitted for acute HF. Methods and results: This retrospective study was performed in 1941 elderly patients aged ≥65 years or older from the cardiovascular physiotherapy for acute HF patients in the Tokyo metropolitan area registry and excluded those who died in hospital. HAD was defined as any decline in the Barthel index (BI) before discharge compared with the BI within 1 month before hospital admission. The primary outcome of this study was all‐cause death and HF readmission. A total of 565 (29%) deaths and 789 (41%) HF readmission occurred over a median follow‐up period of 1.7 years. A total of 476 patients (25%) had HAD during hospital stay after acute HF. In multivariable analysis, HAD predicted all‐cause death [hazard ratio (HR): 1.772; 95% confidence interval (CI): 1.450–2.167; P < 60; 0.001] and with risk of HF readmission (HR: 1.193; 95% CI: 1.005–1.416; P = 0.043) after adjusting for the Meta‐analysis Global Group in Chronic Heart Failure risk score. Conclusions: Hospital‐acquired disability is associated with an increased risk of all‐cause death and readmission for HF in elderly patients with acute HF.